Pregnancy with Wilson’s disease - Devraj, Nandeesha Thindlu; Ramalingappa, Padmasri; Shukla, Aishwarya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Wilson’s disease is a rare, autosomal recessive disorder characterized by impaired liver metabolism of copper, leading to decreased biliary excretion and incorporation of ceruloplasmin levels mainly in the liver and brain. Untreated Wilson’s disease has been shown to cause subfertility and miscarriages. Pregnancy management in women with Wilson’s disease remains an important clinical problem. Early recognition and effective management can help prevent the disease progression and hence give eventful progress and perinatal outcomes. We hereby report the case of a 29-year-old pregnant multigravida with known case of Wilson’s disease since childhood, and on treatment with copper chelating agents and zinc sulphate. She was followed up from early pregnancy till delivery at our hospital. She was monitored in combined obstetric, medicine and neurology clinic. Her pregnancy and postpartum course remained uneventful. She had a spontaneous vaginal delivery at 38+5 weeks period of gestation and gave birth to healthy female baby of 2.66 kg in weight. The infant was genetically screened and was found to be carrier free. It is relatively safe for women with Wilsons disease to become pregnant. Patients with Wilson’s disease receiving regular treatment who remain asymptomatic are usually able to conceive and achieve successful outcomes. However, these pregnancies should be considered as high risk and merit regular surveillance.